2015
DOI: 10.4149/neo_2015_008
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 overexpression is associated with cisplatin resistance in non-small cell lung cancer and mediates sensitivity to cisplatin in A549 cells via the JNK/mitochondrial pathway

et al.

Abstract: The Forkhead box M1 transcription factor (FoxM1) is essential for DNA replication and mitosis, and has important role in cell proliferation and apoptosis. To assess the role of FoxM1 in chemoresistance, we investigated FoxM1 protein expression and the correlation between FoxM1 expression, sensitivity to cisplatin-based therapy, and the survival of non-small cell lung cancer (NSCLC) patients. We generated a cisplatin-resistant lung cancer cell line (A549/CDDP) that showed elevated expression levels of FoxM1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Reports indicate that numerous signaling pathways, such as the Wnt (23), p38 MAPK (40), PI3K/ Akt (41) and TGFβ/Smad2/STAT3/STAT5 pathways (42), are involved in the complex mechanism of DDP resistance. It is also worth mentioning that cell autophagy by hypoxia induced or exacerbated by FOXM1 (43) via the JNK/mitochondrial pathway (44), may decrease the susceptibility of lung cancer cells to cisplatin-induced apoptosis (45). Large numbers of surveys indicate the complexity of the mechanism underlying the regulation of cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that numerous signaling pathways, such as the Wnt (23), p38 MAPK (40), PI3K/ Akt (41) and TGFβ/Smad2/STAT3/STAT5 pathways (42), are involved in the complex mechanism of DDP resistance. It is also worth mentioning that cell autophagy by hypoxia induced or exacerbated by FOXM1 (43) via the JNK/mitochondrial pathway (44), may decrease the susceptibility of lung cancer cells to cisplatin-induced apoptosis (45). Large numbers of surveys indicate the complexity of the mechanism underlying the regulation of cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the MAPK pathway in regulating apoptosis of cancer cells, particularly in drug-resistant cancer cells is complex. A previous study showed p38 MAPK activation was associated with apoptosis induction in A549/DDP cells [20], and another report indicated that JNK activation may contribute to apoptosis in A549/DDP cells [21]. Therefore, further studies are required to elucidate the link between MAPK signaling and apoptosis during HVJ-E induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Through TEAD interaction YAP controls a set of genes such as CTGF, cyr61, survivin, amphiregulin and AXL [11,14,46], and some of them have been associated with drug resistance [47]. [12], and it has been related to the drug resistance in a variety of cancers [48][49][50].…”
Section: Discussionmentioning
confidence: 99%